2023
DOI: 10.1002/adfm.202300021
|View full text |Cite
|
Sign up to set email alerts
|

White Light and Color‐Tuning Long Persistent Luminescence from Metal Halide Based Metal‐Organic Frameworks

Abstract: Room temperature phosphorescence (RTP) materials with long persistent luminescence (LPL) have raised particular attention among researchers for their potential uses in chemical sensing, optical recording devices, biological imaging, and security systems applications, due to the long‐lived triplet states. In this study, one‐pot method of reaction of appropriate ratio of crown ether ligand (15‐Crown‐5) and metallic salts (CdX2) is utilized to yield three metal halide‐based complexes (namely 15‐5‐CdCl2, 15‐5‐CdBr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…[ 1–6 ] Many efforts have been contributed to the design of materials with highly efficient RTP via the strategy of enhancing the intersystem crossing (ISC) rate and stabilizing triplet excitons for long‐lived lifetimes, especially in the molecular crystalline materials due to their highly ordered structures. [ 7–12 ] In this respect, many families of crystalline systems, including one‐component organic crystals, [ 13–16 ] hybrid halides, [ 17–20 ] and metal‐organic complexes, [ 21–24 ] have been developed with efficiently persistent emission and prolonged lifetimes. More recently, stimuli‐responsive RTP complexes are attracting more attention for their importance in constructing smart luminescent switches and developing optical logical gates.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–6 ] Many efforts have been contributed to the design of materials with highly efficient RTP via the strategy of enhancing the intersystem crossing (ISC) rate and stabilizing triplet excitons for long‐lived lifetimes, especially in the molecular crystalline materials due to their highly ordered structures. [ 7–12 ] In this respect, many families of crystalline systems, including one‐component organic crystals, [ 13–16 ] hybrid halides, [ 17–20 ] and metal‐organic complexes, [ 21–24 ] have been developed with efficiently persistent emission and prolonged lifetimes. More recently, stimuli‐responsive RTP complexes are attracting more attention for their importance in constructing smart luminescent switches and developing optical logical gates.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of Ag 6 –NCs/NMP/H 2 O powder at f NMP = 90% was 11.77 μs, 21 times longer than that of Ag 6 –NCs, with a QY of 17.6%, 7.7 times higher than Ag 6 –NCs (Table and Figure e). The microsecond lifetime and large Stokes shift of Ag 6 –NCs/NMP/H 2 O powder indicated that its luminescence is essentially phosphorescence emission …”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, they can increase the spin–orbit coupling of the system through the heavy-atom effect to promote the efficiency of intersystem crossing from the singlet to the triplet state. On the other hand, they can restrict the vibration and rotation of the molecule through coordination interactions to suppress the nonradiative transition of the triplet excitons. , Despite this, there are limited reports on functional MOF materials that integrate LPL and the stimulus response.…”
Section: Introductionmentioning
confidence: 99%